Pengaruh Waktu Pencahayaan Terhadap Performa Ayam Pedaging (Broiler) - Sadi, Ristasari; Nuhon, Kornelius Liat (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
Lighting is an important management technique in broiler rearing to increase growth.Because light is very influential on the development of cells - body cells, feed efficiency,physiological processes and behavior of chickens. The purpose of this study was todetermine the effect of lighting timing on broiler performance. This study used a completelyrandomized design (CRD) with 4 treatments and 3 replications. With the treatmentarrangement: P0 (24 hours of lighting), P1 (22 hours of lighting), P2 (20 hours of lighting), P3(18 hours of lighting). The results obtained in this study were the amount of feedconsumption in the P0 and P1 treatments was lower than the P2 and P3 treatments. Thishappened because P2 (24 hours of light) and P1 (22 hours of lighting) caused the chickensto be active both at night and during the day so as to reduce feed consumption, Weight Gain(PBB) increased from P0, P2 to P3 and decreased PBB at P1. This is because the darkconditions at P2 and P3 caused the chickens to tend to reduce movement, the lowest ormost efficient broiler feed conversion was achieved by treatment P0 (24 hours of lighting)with a conversion of 1.47 while the highest in treatment P1 was 1.57 although statistically didnot show a significant difference.